Effectiveness and safety of massage for athletic injuries: A protocol for systematic review and meta-analysis. Issue 32 (13th August 2021) - Guo, Guangxin; Xie, Shengji; Cai, Feihong; Zhou, Xu; Xu, Jianghan; Wu, Boyi; Wu, Guanghui; Xiao, Ran; Xu, Xiruo; Lu, Ping; Fang, Min
Abstract: Background: Athletic injuries have been a major area of interest in the field of sports and clinical medicine. Implemented on people's skin, muscles, and joints as an important part of complementary and alternative medicine (CAM), massage therapy has a positive effect on athletic injuries. This protocol is to provide the methods used to evaluate the effectiveness and safety of massage therapy for patients with athletic injuries. Methods: A systematic search will be performed in the following electronic databases for randomized controlled trials (RCTs) to evaluate the effectiveness and safety of massage therapy in treating athletic injuries: PubMed, the Cochrane Library, EMBASE and four Chinese databases (CNKI, Wan Fang, CBMdisc and VIP). Each database will be searched from inception to July 2021. The entire process will include study selection, data extraction, risk of bias assessment and meta-analysis. Results: A high-quality synthesis of current evidence of massage therapy for patients with athletic injuries will be provided. Conclusions: This systematic review will provide evidence for assessing the credibility of massage therapy for patients with athletic injuries. Dissemination and ethics: The results of this review will be disseminated through peer-reviewed publication. This review does not require ethical approval because all the data used in this systematic review and meta-analysis have already been published. Furthermore, all of these data will be analyzed anonymously during the review process. INPLASY registration number: INPLASY202170066.